Mechanisms of Selenium Enrichment and Measurement in Brassicaceous Vegetables, and Their Application to Human Health - Wiesner-Reinhold, Melanie; Schreiner, Monika; Baldermann, Susanne; Schwarz, Dietmar; Hanschen, Franziska S.; Kipp, Anna P.; Rowan, Daryl D.; Bentley-Hewitt, Kerry L.; McKenzie, Marian J. (Frontiers in Plant Science, 2017)
Selenium (Se) is an essential micronutrient for human health. Se deficiency affects hundreds of millions of people worldwide, particularly in developing countries, and there is increasing awareness that suboptimal supply of selenium can also negatively affect human health. Selenium enters the diet primarily through the ingestion of plant and animal products. Although plants are not dependent on Se they take it up from the soil through the sulfur (S) uptake and assimilation pathways. Therefore, geographic differences in the availability of soil Se and agricultural practices have a profound influence on the Se content of many foods, and there are increasing efforts to biofortify crop plants with Se. Plants from the Brassicales are of particular interest as they accumulate and synthesize Se into forms with additional health benefits, such as methylselenocysteine (MeSeCys). The Brassicaceae are also well known to produce the glucosinolates; S-containing compounds with demonstrated human health value. Furthermore, the recent discovery of the selenoglucosinolates in the Brassicaceae raises questions regarding their potential bioefficacy. In this review we focus on Se uptake and metabolism in the Brassicaceae in the context of human health, particularly cancer prevention and immunity. We investigate the close relationship between Se and S metabolism in this plant family, with particular emphasis on the selenoglucosinolates, and consider the methodologies available for identifying and quantifying further novel Se-containing compounds in plants. Finally, we summarise the research of multiple groups investigating biofortification of the Brassicaeae and discuss which approaches might be most successful for supplying Se deficient populations in the future.